Strategy Use and Language Performance by Second Language Learners in Nigeria - Ogenyi, Laz C. (Scientific Research Publishing, 2016)
It is commonly believed that Nigerian students perform very poorly in the English language. Many reasons adduced to be the causative variables for students’ poor performance in the English language are located away from the students themselves. What the above scenario portends is that no effort has been made to find out the strategies which the students themselves use in their efforts to learn the English language; it also implies that no effort has been made to find out the relationship between such strategies and the level of students’ performance in the target language. The problem which this study addressed was not only to evaluate the language learning strategies which the sampled study population use in their efforts to learn English, but also to determine the extent to which their mean achievement scores in English depend on their use of various language learning strategies. The study was carried out using a descriptive survey research design. Its population consisted of Senior Secondary School (SSS) form II students in three states of south-eastern Nigeria. Random sampling technique was used to select a total of one thousand, four hundred and one (1401: 747 = males, 654 = females) students used for the study. Two sets of instrument were used to collect data for the investigation: appraisal instrument (cloze test), and questionnaire. Two research questions and corresponding two null hypotheses were formulated to guide the study. Results of the study revealed that 1) the greatest proportion of the Igbo learners of English in SSS II (84.3%) made use of socio-affective language learning strategy, while cognitive strategy had the lowest proportion of users (50.9%); 2) there was a significant difference, in the English language performance, between the users and non-users of the various language learning strategies.
Keywords: English Language Learning; Igbo Language Learners; Strategy Use and Language Performance; Second Language Learners in Nigeria